Jurnal Hukum KAJIAN YURIDIS PENETAPAN LAHAN MASYARAKAT SEBAGAI TAMAN WISATA ALAM SEBLAT YURISDIKSI AIR RAMI KABUPATEN MUKOMUKO: Perlindungan Hukum Hak Atas Tanah Masyarakat dengan Ditetapkan Sebagai Kawasan Taman Wisata Alam - Putra, Deyan Ajian; Sauni, Herawan (UNIB Press, 2024)
Legal issues that occur in the community are related to land tenure issues. On the one hand, land rights are protected by legislation, especially customary rights and property rights. On the other hand, the designation of an area as a Nature Tourism Park must have a certain landscape uniqueness. However, empirical facts show that the designation of Dusun Pulau village community land into the Seblat TWA area is not in accordance with and does not meet the criteria for natural resources determined by law and allegedly does not pay attention to land rights owned by the community. This research examines the validity of the determination of community land into a natural tourist park, especially in the jurisdiction of Mukomuko district. The method used in this research is empirical law and supported by normative legal research with qualitative methods and utilising data collected through primary and secondary sources, literature reviews and interviews both directly and via telephone. The results showed that the Seblat TWA area in the jurisdiction of Mukomuko district did not have natural uniqueness that met the criteria contained in the applicable regulations, besides that the determination was allegedly carried out unilaterally without regard to land rights owned by the community. Keywords: Land rights, Nature Tourism Park (TWA), Validity.